The relationship between the use of technology in learning and student self-efficacy - Putri, Nimas Dahlia; Abtasari, Selly Moza; Izazi, Fathan Cahyan; Nurhidayah, Nurhidayah; Tanjung, Romi Fajar; AR, Silvia (Journal of Counseling and Educational Research, 2024)
Information technology and self-efficacy in learning activities are very important, because information technology is a process that can help to make it easier to access and obtain the desired scientific information. The aim of the research is to determine the level of technology use in learning and the level of student self-efficacy and to examine the relationship between the use of technology in learning and student self-efficacy. The method applied in this research adopts a quantitative approach with a correlational type. This study had 34 samples determined using random sampling techniques. The research results show that the level of skills in using technology in learning and students' self-efficacy are generally in the medium category. Then it can be seen that the correlation between variables does not show a significant correlation.